Characterization of Chicken Eggshell-Derived Hydroxyapatite/Zeolite Composite as a Methylene Blue Absorbent - Nur Safitriani; Kurnia Ramadani; Sitti Chadijah; Syarifah Rabiatul Adawiah; Titik Andriani; Firnanelty Firnanelty (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Purebred chicken eggshell is a promising natural source because it contains high calcium carbonate (CaCO3), which is used as a hydroxyapatite (HAp) precursor, with natural abundance and biodegradability, making it an eco-friendly alternative to synthetic materials. HAp is relevant for dye removal because of its high adsorption capacity, chemical stability, and ability to interact with dye molecules through ion exchange and surface interactions with the material. The composite adsorbent of Hap-zeolite is effective for wastewater treatment based on the result of HAp-zeolite composite's adsorption capacity against methylene blue. Methylene blue is one of the dyeing wastes originating from the textile industry. The method of synthesis of Hap used precipitation. The FTIR characterization results showed OH groups at wavenumber 3434 cm-1, CO32- group with wavenumber 1421 cm-1, PO43- bending group with wavenumber 565 cm-1, and PO43- stretching at wavenumber 1035 cm-1. The highest peak XRD yield at an angle of 2θ=34.04º corresponds to a hexagonal crystal formed. The adsorption process is carried out with a HAp-zeolite mass ratio of 4:2 (w/w), with contact times for 180 minutes, resulting in the best adsorption efficiency around 99.99% measured via UV-Vis spectrophotometry. The results indicate that HAp-zeolite composites are highly effective for methylene blue removal and have potential application in wastewater treatment.